IGFBP7 Induces Differentiation and Loss of Survival of Human Acute Myeloid Leukemia Stem Cells without Affecting Normal Hematopoiesis - Han J.M.P. Verhagen; Noortje van Gils; Tania Martiañez; Anna van Rhenen; Arjo Rutten; Fedor Denkers; David C. de Leeuw; Marjon A. Smit; Mei-Ling Tsui; Louise L.E. de Vos Klootwijk; Renee X. Menezes; Meyram Çil; et al. (Cell Reports, 2018)
Summary: Leukemic stem cells (LSCs) are thought to be the major cause of the recurrence of acute myeloid leukemia (AML) due to their potential for self-renewal. To identify therapeutic strategies targeting LSCs, while sparing healthy hematopoietic stem cells (HSCs), we performed gene expression profiling of LSCs, HSCs, and leukemic progenitors all residing within the same AML bone marrow and identified insulin-like growth factor-binding protein 7 (IGFBP7) as differentially expressed. Low IGFBP7 is a feature of LSCs and is associated with reduced chemotherapy sensitivity. Enhancing IGFBP7 by overexpression or addition of recombinant human IGFBP7 (rhIGFBP7) resulted in differentiation, inhibition of cell survival, and increased chemotherapy sensitivity of primary AML cells. Adding rhIGFBP7 reduced leukemic stem and/or progenitor survival and reversed a stem-like gene signature, but it had no influence on normal hematopoietic stem cell survival. Our data suggest a potential clinical utility of the addition of rhIGFBP7 to current chemotherapy regimens to decrease AML relapse rates. : Verhagen et al. show that AML leukemic stem cells have lower IGFBP7 expression, which is associated with lower sensitivity to chemotherapy. IGFBP7 overexpression or addition of recombinant human IGFBP7 affects the survival of primary AML stem cells, but it does not affect normal hematopoietic stem cells. Keywords: acute myeloid leukemia, IGFBP7, leukemic stem cells, hematopoietic stem cells, chemotherapy sensitivity